Strategic Methods for Raising Awareness of Climate Change: Improving Organizational Sustainability and Education - Indrian Supheni; Ambarwati; Fatika Firli Fitrohani (Proceeding International Conference on Digital Education and Social Science, 2024)
One of the most critical issues of the twenty-first century is climate change, which calls for immediate action from all facets of society. This research explores strategic approaches to enhancing climate change awareness through educational systems and organizational practices, focusing on fostering sustainability. The study looks at how corporations and academic institutions can include climate change awareness into their primary operations to influence future generations' perspectives and the sustainability plans of private companies and governmental organizations. The research employs a mixed-methods approach, combining qualitative analysis of case studies from educational programs and organizational sustainability initiatives with quantitative surveys on the effectiveness of climate change integration into curricula and corporate practices. This study finds best practices that have resulted in noticeable gains in climate awareness and sustainable outcomes by examining essential factors such as leadership commitment, policy frameworks, interdisciplinary education techniques, and stakeholder involvement. This study gives valuable information for teachers, business leaders, and lawmakers looking to make climate change rules that support social and environmental sustainability. The study encourages a more joined-up approach to addressing climate change by connecting business actions with education, ensuring a sustainable future for all.